COMPARATIVE ANALYSIS OF CURRENT AND VOLTAGE-CONTROLLED PHOTOVOLTAIC MAXIMUM POWER POINT TRACKING - Sobreira, Pedro de Assis; Villalva, Marcelo Gradella [UNESP]; Barbosa, Pedro Gomes; Carvalho Braga, Henrique Antonio; Gazoli, Jonas Rafael; Ruppert, Ernesto; Ferreira, Andre Augusto; IEEE (Ieee, 2011)
Maximum Power Point tracking (MPPT) in photovoltaic (PV) systems may be achieved by controlling either the voltage or current of the PV device. There is no consensus in the technical literature about how is the best choice. This paper provides a comparative analysis performance among current and voltage control using two different MPPT strategies: the perturb and observe (P&O) and the incremental conductance techniques.
Keywords: photovoltaic system; maximum power point tracking; MPPT; current control; voltage control